Motivation - A Stimulating Factor for Increasing Human Resource Management Performance - Emanoil MUSCALU; Silvana MUNTEAN (Revista de Management Comparat International)
Motivation is the basis of behaviors and activities that people deliver inside the association in relation to the peculiarity of the challenges that follow a category or another of functional relations. Thus, in order to assure the performance of the modern associations there is the need to know and understand the elements that motivate or demotivate an employee and even more, to apply them. Individual and constructional performance is in direct relationship with the direct implementation of the management of human resources. Thus, only by knowing the motivational theories and by applying efficient managerial strategies in order to engage the employees in competitive achievement of the organization's objectives there can be created a structural background which can help the interests of the organization as well as the ones of the employees.